Hayes' handbook of pesticide toxicology / edited by Robert I. Krieger ; associate editors, John Doull ... [et al.]. - Krieger, Robert Irving, 1943-; Hayes, Wayland J., 1917-1993. (Amsterdam : Elsevier, 2010)
The Handbook of Pesticide Toxicology is a comprehensive, two-volume reference guide to the properties, effects, and regulation of pesticides that provides the latest and most complete information to researchers investigating the environmental, agricultural, veterinary, and human-health impacts of pesticide use. Written by international experts from academia, government, and the private sector, the Handbook of Pesticide Toxicology is an in-depth examination of critical issues related to the need for, use of, and nature of chemicals used in modern pest management. This updated third edition carries on the book's tradition of serving as the definitive reference on pesticide toxicology and recognizies the seminal contribution of Wayland J. Hayes, Jr., co-Editor of the first edition. Feature: Presents a comprehensive look at all aspects of pesticide toxicology in one reference work. Benefit: Saves researchers time in quickly accessing the very latest definitive details on toxicity of specific pesticides as opposed to searching through thousands of journal articles. Feature: Clear exposition of hazard identification and dose response relationships in each chapter featuring pesticide agents and actions Benefit: Connects the experimental laboratory results to real-life applications in human health, animal health and the environment. Feature: All major classes of pesticide considered. Benefit: Provides relevance to a wider variety of researchers who are conducting comparative work in pesticides or their health impacts. Feature: Different routes of exposure critically evaluated. Benefit: Connects the loop between exposure and harmful affects to those who are researching the affects of pesticides on humans or wildlife.
78. Symmetrical and Asymmetrical Triazine Herbicides -- 79. Phenylurea Herbicides -- 80. Protoporphyrinogen Oxidase-Inhibiting Herbicides -- 81. Chloracetanilides -- 82. Paraquat -- 83. Phenoxy Herbicides -- 84. Dicamba -- 85. Imidazolinones -- 86. Toxicology of Triazolopyrimidine Herbicides -- 87. A Toxicological Assessment of Sulfur as a Pesticide -- 88. Cyprodinil: A Fungicide of the Anilinopyrimidine Class -- 89. Captan and Folpet -- 90. Mammalian Toxicokinetics and Toxicity of Chlorothalonil -- 91. Inhibitors of Aromatic Acid Biosynthesis -- 92. Toxicology of DDT and Some Analogs -- 93. Boric Acid and Inorganic Borate Pesticides -- 94. Imidacloprid: A Neonicotinoid Insecticide -- 95. Interactions with the gamma-Aminobutyric Acid A-Receptor: Polychlorocycloalkanes and Recent Congeners -- 96. The Role of P-glycoprotein in Preventing Developmental and Neurotoxicity: Avermectins -A Case Study -- 97. DEET -- 98. The Safety Assessment of Piperonyl Butoxide -- 99. Rodenticides -- 100. Toxicology and Safety Evaluation of the New Insect Repellent Picaridin (Saltidi{u2BA9} -- 101. Ryanodine Receptor Activators -- 102. Sulfuryl Fluoride -- 103. Phosphine -- 104. Methyl Bromide -- 105. 1,3-Dichloropropene -- 106. Metam-Sodium -- 107. Methyl iodide.
Rev. ed. of: Handbook of pesticide toxicology. 2nd ed. / edited by Robert I. Krieger. 2001.
Keywords: Pesticides -- toxicity